Molecular Identification of Non-tuberculous Mycobacterial Species in Fecal samples from Cattle and Buffaloes - Slathia, Pallavi; Narang, Deepti; Chandra, Mudit (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Abstract: The non-tuberculous mycobacteria (NTM) are ‘atypical mycobacteria’ belonging to species other than those classified in the Mycobacterium tuberculosis complex. NTM species have been reported to cause cross-reactive immune responses that interfere with the diagnosis of tuberculosis in both livestock and wildlife and are considered as potential pathogens for animals and humans. The present study was conducted for detection of non- tuberculous mycobacterial species (NTM) in fecal samples with a history of intermittent diarrhea from cattle and buffaloes. Polymerase Chain Reaction and PRA (PCR-RFLP) was performed on 30 fecal samples collected from cattle and buffaloes of organized dairy farms in Ludhiana, for detection of non - tuberculous mycobacterial species (NTM). In the present studyM. fortuitum was detected in two out of 30 fecal samples by PCR and PCR-RFLP (PRA).
Keywords: M. fortuium; Non-tuberculous Mycobacteria (NTM); Polymerase Chain Reaction (PCR); PRA (Polymerase Chain Reaction-Restriction Fragment Length Polymorphism Analysis )